Seismic response to evolving injection at the Rotokawa geothermal field, New Zealand. (May 2020) - Hopp, Chet; Sewell, Steven; Mroczek, Stefan; Savage, Martha; Townend, John
Highlights: We present a catalog of more than 25, 000 microseismic events for a 4 year period at the Rotokawa geothermal field. The catalog delineates two kilometer scale reservoir structures, one of which had not previously been observed from microseismic locations. The rate of seismicity shows no dependence on injectivity changes in the injection field. The earthquake b -value ranges between ∼0.5 and ∼1.6 and is greater near the injection wells, potentially due to a wider distribution of activated fractures. Abstract: Catalogs of microseismicity are routinely compiled at geothermal reservoirs and provide valuable insights into reservoir structure and fluid movement. Hypocentral locations are typically used to infer the orientations of structures and constrain the extent of the permeable reservoir. However, frequency-magnitude distributions may contain additional, and underused, information about the distribution of pressure. Here, we present a four-year catalog of seismicity for the Rotokawa geothermal field in the central Taupō Volcanic Zone, New Zealand starting two years after the commissioning of the 140 MWe Nga Awa Purua power station. Using waveform-correlation-based signal detection we double the size of the previous earthquake catalog, refine the location and orientation of two reservoir faults and identify a new structure. We find the rate of seismicity to be insensitive to major changes in injection strategy during the study period, including the injectivity decline and shift of injection away from the dominant injector, RK24. We also map the spatial distribution of the earthquake frequency-magnitude distribution, or b -value, and show that it increases from ∼1.0 to ∼1.5 with increasing depth below the reservoir. As has been proposed at other reservoirs, we infer that these spatial variations reflect the distribution of pressure in the reservoir, where areas of high b -value correspond to areas of high pore-fluid pressure and a broad distribution of activated fractures. This analysis is not routinely conducted by geothermal operators but shows promise for using earthquake b -value as an additional tool for reservoir monitoring and management.